Ceramic firing protocols and thermocycling: effects on the load-bearing capacity under fatigue of a bonded zirconia lithium silicate glass-ceramic - Diniz, Vandeberg [UNESP]; Condé Oliveira Prado, Pedro Henrique [UNESP]; Meireles Rodrigues, Jonas Vinicius [UNESP]; Monteiro, Jaiane Bandoli [UNESP]; Zucuni, Camila; Valandro, Luiz Felipe; Melo, Renata M. [UNESP] (Elsevier, 2020)
This study evaluated the effect of different firing processes (without firing, additional crystallization and glaze firing) and thermal-cycling (with or without) on the fatigue behavior of simplified zirconia-lithium silicate (ZLS) glass ceramic restorations cemented to a dentin-like material. Materials and Methods. One hundred twenty-nine (129) discs (diameter = 12 mm and thickness = 1.2 mm) of ZLS (Celtra Duo, Dentsply Sirona) and fiber-reinforced epoxy resin (diameter = 12 mm and thickness = 2.3 mm) were produced and tested under fatigue according to 2 study factors: a firing protocol with 3 levels (without firing, additional crystallization and glaze firing) and thermocycling of 2 levels (absence/presence), composing 6 study groups. Ceramic and epoxy resin discs had their surfaces treated and adhesive cementation was performed (Multilink N, Ivoclar). Half of the samples were immediately tested; the other half were subjected to thermal-cycling (10,000 cycles in water; 5-55 °C). The staircase method determined the fatigue failure load (100,000 cycles at a frequency of 20 Hz). The fatigue data (in N) were submitted to 2-way ANOVA and Bonferroni test (p < 0.05). Fractographic analyses were also carried out. Thermocycling decreased the fatigue failure load (FFL) of all groups when compared to those without aging. Bonferroni's test indicated that the groups with crystallization/glazing process behaved better in terms of FFL than those without firing in the same storage condition. All the samples had radial cracks and all fractures originated from defects on the cementation surface of the ceramic discs. Crystallization and glaze firing had a positive effect on the fatigue failure load of adhesively cemented ZLS glass ceramic compared to the group without crystallization firing, in both storage conditions (with or without thermocycling).
Keywords: Aging; Crystallization; Fatigue; Glass ceramics